SUGGESTIONS FOR THE EVALUATING OF RAILWAY DEFORMATION - Bondarenko, I. O. (Science and Transport Progress, 2008)
It is offered to bring in a criterion on an estimation of deformation capability of a railway track. The offers on itsvalues are given